Hubungan Mutu Pelayanan Dengan Kepuasan Pasien BPJS Kesehatan Di Unit Rawat Inap RSUD Tengku Rafi’an Kabupaten Siak - Jihan Natassa; Silvia Sri Dwijayanti (STIKes Payung Negeri Pekanbaru, 2019)
Abstract In realizing patient satisfaction one aspect that must be considered is the quality of health services that will be provided to patients, the quality of health services is the degree of perfection of services for health services in accordance with professional standards and service standards. The purpose of this study was to determine the relationship of service quality with BPJS patient satisfaction in the Inpatient Unit of Tengku Rafi'an Hospital Siak District in 2018. This type of research is a quantitative descriptive study with Cross Sectional design. The results showed Physical (Tangible) P- value 0.003 P-value Reliability 0.044, P-value Responsiveness 0.001, P-value Assurance 0.037, P-value empathy 0.002. It can be concluded, there is a relationship between the quality of service with BPJS Health patient satisfaction in the Inpatient Unit of Siak Regional General Hospital in 2018. It is expected that the results of this study can be used as input for Siak Regional General Hospital in order to improve patient satisfaction. Bibliography : 25 (2006-2017) Keywords : Service Quality, Patient Satisfaction